Psychological readiness for professional activity and emotional intelligence: development peculiarities among students of socionomic professions - TYNDYK, Yana (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2023)
Background. The war in the East of Ukraine exacerbated the need for high-quality training of specialists in socionomy to serve the population affected by this war. After all, working with those who have manifested post-traumatic stress disorder requires from the professionals not only psychological readiness to help people but also a high level of emotional intelligence development. It affects the efficiency of their professional activities and increases their resistance to emotional exhaustion and professional burnout. The results of a theoretical and empirical study of the relationship between the psychological features of emotional intelligence and the components of psychological readiness for socio-economic professions are presented, the differences between the features of emotional intelligence and psychological readiness in different groups of subjects (future psychologists, teachers and doctors) are indicated. Methods. The study used research methods and psychodiagnostic tests to assess the development level of psychological readiness and emotional intelligence components. Results. Results of the study: a significant number of students had a low development level of psychological readiness components; more than a third of socionomic students show a low level of emotional intelligence development; emotional intelligence (and its individual components) is in some way associated with personal factors (16 PF-Questionnaire by Cattell), particularly with the factors B, C, G, H, N, Q2, Q3 - positive correlation, with factors L, Q1 - negative correlation; the differences between the indicators of emotional intelligence and psychological readiness for socionomic professions among future psychologists, physicians and educators are determined; the directions of emotional intelligence influence on components of psychological readiness are revealed. Conclusions. The study’s results will help improve the psychological training process of socionomic specialists in higher education institutions, as these results point to problems that need to be worked out to better prepare each student for professional work.